2019
DOI: 10.1038/s41431-019-0387-4
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder views and attitudes towards prenatal and postnatal transplantation of fetal mesenchymal stem cells to treat Osteogenesis Imperfecta

Abstract: The Boost Brittle Bones Before Birth (BOOSTB4) clinical trial is investigating the safety and efficacy of transplanting fetal derived mesenchymal stromal cells (MSCs) prenatally and/or in early postnatal life to treat severe Osteogenesis Imperfecta (OI). This study aimed to explore stakeholder views to understand perceived benefits or concerns, identify ethical issues and establish protocols for support and counselling. Semi-structured qualitative interviews were conducted with three groups; 1. Adults affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Postnatal transplantation with same-donor foetal liver MSCs was performed at 1.6 years of age, and following the procedure, a resumption of vertical growth was observed. Based on these clinical experiences, the first clinical trial of the transplantation of foetal liver MSCs, the Boost Brittle Bones Before Birth (BOOSTB4) trial is ongoing [ 99 , 100 ]. The BOOSTB4 trial is investigating the safety and tolerability of MSC transplantation as a therapy for severe forms of OI (OI type 3 and 4).…”
Section: Managementmentioning
confidence: 99%
“…Postnatal transplantation with same-donor foetal liver MSCs was performed at 1.6 years of age, and following the procedure, a resumption of vertical growth was observed. Based on these clinical experiences, the first clinical trial of the transplantation of foetal liver MSCs, the Boost Brittle Bones Before Birth (BOOSTB4) trial is ongoing [ 99 , 100 ]. The BOOSTB4 trial is investigating the safety and tolerability of MSC transplantation as a therapy for severe forms of OI (OI type 3 and 4).…”
Section: Managementmentioning
confidence: 99%
“…*Microarray testing would be initiated in tandem with prenatal ES. † Such as prenatal mesenchymal stem cell transplants by in utero transfusion in OI (BOOST4 study) 65 …”
Section: Existing Prospective Prenatal Exome Sequencing Studiesmentioning
confidence: 99%
“…† Such as prenatal mesenchymal stem cell transplants by in utero transfusion in OI (BOOST4 study). 65 …”
Section: Existing Prospective Prenatal Exome Sequencing Studiesmentioning
confidence: 99%
“…Furthermore, MSC transplantation in OI patients has showed promising results leading to increased BMD and decreased fracture risk after transplantation in both mice and humans ( 18 21 ). In 2016, EU approved the Boost Brittle Bones Before Birth (BOOSTB4) study whose sole aim is to perform Phase I/II clinical trials on the safety and efficacy of prenatal and/or postnatal transplantation of fetal-derived MSC for severe forms of OI (Type III and IV) ( 22 ). Finally, it has been also shown that allele-specific Col1a1 and Col1a2 silencing using small interfering RNAs leads to reduction of the mutant collagen in both human and mice cell models ( 23 , 24 ).…”
Section: What Have We Learned From Monogenic Skeletal Disorders?mentioning
confidence: 99%